Differential Diagnosis of Metastases in Bone Scans: Chemotherapy induced Bone Necrosis - Reuland, P.; Kaiserling, E.; Klingebiel, T.; Feine, U.; Niethammer, D. (Nuklearmedizin - NuclearMedicine, 1999)
Aim: Influenced by the incorrect diagnosis of a bone metastasis caused by bone necrosis we evaluated reasons and frequency of bone necrosis in patients referred for bone scanning in follow-up of tumors. Methods: Bone scans performed within two years on patients with primary bone tumors or tumors metastatic to bone were reviewed in respect to the final diagnosis bone necrosis. Results: We found the cases of three young patients who presented the appearance of hot spots on bone scintigrams which were finally diagnosed as bone necrosis. In two cases the diagnosis was based on histological findings, in one case the diagnosis was made evident by follow-up. All the three patients had been treated by chemotherapy and presented no other reason for the development of bone necrosis. Enhanced tracer uptake in all sites decreased within eight weeks up to two years without therapy. Conclusion: Single and multiple hot spots after chemotherapy may be originated by bone necrosis but mimikry metastases.
Keywords: Bone necrosis; bone metastasis; bone scintigram; follow-up